COSMC-Regulated O-Glycosylation: A Bioinformatics-Driven Biomarker Identification for Stratifying Glioblastoma Stem Cell Subtypes - Sara Sadat Aghamiri; Rada Amin (Kinases and Phosphatases)
Glioblastoma stem cells (GSCs) are key drivers of relapse, metastasis, and therapy resistance in glioblastoma due to their adaptability and diversity, which make them challenging to target effectively. This study explores the O-glycosylation in differentiating two key GSC subtypes, CD133 and CD44. We utilized the TCGA dataset of GBM and presented the reproducible bioinformatics analysis for our results. Our profiling showed enriched O-glycosylation signatures in CD44-expressing GBM cells over CD133, with Cosmc, the chaperone for core mucin-type O-glycosylation, significantly upregulated in the CD44-positive group. Moreover, Cosmc was associated with shorter progression-free intervals, suggesting its potential as an indicator of aggressive disease. High Cosmc expression also enriched immune-related pathways, including inflammatory response and antigen presentation, and was associated with presence of myeloid cells, T cells, and NK cells. Additionally, elevated Cosmc correlated with extracellular matrix (ECM) pathways and stromal cell populations, such as perivascular fibroblasts. These findings position O-glycosylation, specially, Cosmc as a promising biomarker for distinguishing GSC subclones, with relevance to immune modulation, and ECM dynamics, identifying it as a potential target for novel GBM therapies.